The intersecting associations between race and ethnicity, skin color, and perceived unfair treatment by police. Issue 1 (2nd January 2023) - Finkeldey, Jessica G.; Dennison, Christopher R.; Cui, Shiyue
Abstract: This study examines the association between self-identified race and ethnicity, perceived skin color, and ever being unfairly stopped, searched, or questioned by police among a nationally representative sample of Whites, Blacks, Latinos, and other groups. Results show that Non-Latino Blacks and Latinos are more likely to experience unfair police treatment compared with non-Latino Whites. Respondents with medium brown, dark brown, or black skin tones are more likely to report unfair treatment by police than those with white skin. Darker skin is consequential within Latinos, although Black respondents (regardless of color) are among those most likely to experience unfair police treatment.